The safe food imperative: Accelerating progress in low- and middle-income countries - Jaffee, Steven; Henson, Spencer; Unnevehr, Laurian J.; Grace, Delia; Cassou, Emilie (World Bank, 2019)
Food safety hazards are increasingly being recognized as a major public health problem worldwide, yet among developing countries, there is limited understanding of the wider-ranging socio-economic costs of unsafe food and the benefits of remedial or preventative measures. This limited evidence base has led many countries to underinvest in food safety, or invest inefficiently in reaction to serious outbreaks of foodboroe illness, other food scares, or trade interruptions. For many countries experiencing rapid urbanization and dietary changes, the growing complexity of food safety hazards is outpacing if not overwhelming prevailing food safety management capacity-both in government and in supply chains.